2022
DOI: 10.30762/jeels.v8i2.3215
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Learning Approaches in The EFL Emergency Online Learning Context

Abstract: Emergency online learning has transformed today’s learning while opening up opportunities and challenges, one of which is learning approach. This study aims to investigate students’ learning approach in the English Education study program in emergency online learning. A mixed-method was employed using two instruments; R-SPQ-2F questionnaire and semi-structured interviews. The results of the instrument check showed that the R-SPQ-2F survey and interview guide were valid (.90) and reliable (α=.88). Calculated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
(111 reference statements)
1
6
0
Order By: Relevance
“…The right teaching method and style may improve students" interest in the subject. This finding is aligned with Santosa et al (Santosa et al 2021) as students able to think critically when presented with the right questions by their teacher.…”
Section: Supporting and Inhibiting Factors Of Salsupporting
confidence: 88%
See 2 more Smart Citations
“…The right teaching method and style may improve students" interest in the subject. This finding is aligned with Santosa et al (Santosa et al 2021) as students able to think critically when presented with the right questions by their teacher.…”
Section: Supporting and Inhibiting Factors Of Salsupporting
confidence: 88%
“…In the Indonesian context, students are found to achieve academic success through surface approach (Mansir and Karim 2020;Santosa 2018). The study resulted in the learning process is inclined to be teacher centered and students highly respects their teacher as a source of knowledge (Santosa 2017(Santosa , 2018Santosa, Ratminingsih, and Adnyani 2021). Budiarta and Santosa (2020) stated that in the 21 st century, it is important to incorporates technology, innovative way of teaching, and encourage students to be active in their learning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is comparable to that of Astika and Sumakul (2019), who observed that students at a private institution in Central Java adopt a deep approach to English learning. The students from Central Java utilized a learning approach were comparable to what Santosa et al (2021) identified, namely the approach used by English students at a university in Bali to study in the setting of emergency learning.…”
Section: Discussionmentioning
confidence: 99%
“…Based on various studies on student learning approaches that have been carried out, research on learning approaches for EFL junior high school students seems to be still limited. Previous studies have mostly focused on higher education students and some high school students (Astika & Sumakul, 2019;Hussin et al, 2017;Rachmatullah & Ha, 2019;Santosa, Ratminingsih, & Adnyani, 2021;Santosa, 2017;Yueying & Xiaodong, 2016). For example, research on Islamic high school students in Indonesia found a tendency to apply a surface approach (Mulyani, Suherdi, & Sundayana, 2020).…”
Section: Introductionmentioning
confidence: 99%